The Sorption of Th(IV) Ions onto Montmorillonite: The Effect of pH, Ionic Strength and Fulvic Acid - Lei Chen; Xianjin Yu; Zengdian Zhao; Yunhui Dong (Adsorption Science & Technology)
Thorium was considered as a chemical analogue of other tetravalent actinides. The sorption of Th(IV) ions onto montmorillonite and its cross-linked counterpart in the presence/absence of fulvic acid was investigated via a batch technique as a function of pH and fulvic acid concentration. The results obtained indicate that the sorption of Th(IV) ions was strongly dependent on the pH value of its solution, with the presence of fulvic acid enhancing such sorption at low pH values. It was also found that the sorption of Th(IV) ions was dependent on the ionic strength. Cross-linked montmorillonite was found to be a suitable candidate for the sorption and pre-concentration of Th(IV) ions from large volumes of liquid solution. Surface complexation rather than cation exchange mainly contributes to the sorption of Th(IV) ions onto montmorillonite.